Comparative Analysis of Morphology, Photosynthetic Physiology, and Transcriptome Between Diploid and Tetraploid Barley Derived From Microspore Culture - Chen, Yunyun; Xu, Hongwei; He, Ting; Gao, Runhong; Guo, Guimei; Lu, Ruiju; Chen, Zhiwei; Liu, Chenghong (Frontiers in Plant Science, 2021)
Polyploids play an important role in the breeding of plant for superior characteristics, and many reports have focused on the effects upon photosynthesis from polyploidization in some plant species recently, yet surprisingly little of this is known for barley. In this study, homozygous diploid and tetraploid plants, derived from microspore culturing of the barley cultivar “H30,” were used to assess differences between them in their cellular, photosynthetic, and transcriptomic characteristics. Our results showed that tetraploid barley has the distinct characteristics of polyploids, namely thicker and heavier leaves, enlarged stomata size or stomatal guard cell size, and more photosynthetic pigments and improved photosynthesis (especially under high light intensity). This enhanced photosynthesis of tetraploid barley was confirmed by several photosynthetic parameters, including net photosynthetic rate (Pn), stomatal conductance (Gs), intercellular CO2 concentration (Ci), transpiration rate (Tr), maximum net photosynthetic rate (Pmax), light saturation point (LSP), maximum RuBP saturated rate carboxylation (Vcmax), and maximum rate of electron transport (Jmax). Transcriptomic analyses revealed that just ~2.3% of all detected genes exhibited differential expression patterns [i.e., differentially expressed genes (DEGs)], and that most of these – 580 of 793 DEGs in total – were upregulated in the tetraploid barley. The follow-up KEGG analysis indicated that the most enriched pathway was related to photosynthesis-antenna proteins, while the downregulation of DEGs was related mainly to the light-harvesting cholorophyII a/b-binding protein (Lhcb1) component, both validated by quantitative PCR (qPCR). Taken together, our integrated analysis of morphology, photosynthetic physiology, and transcriptome provides evidences for understanding of how polyploidization enhances the photosynthetic capacity in tetraploids of barley.